Computer Science for Equity: Teacher Education, Agency, and Statewide Reform - Goode, Joanna; Skorodinsky, Max; Hubbard, Jill; Hook, James (Frontiers in Education, 2020)
This paper reports on a statewide “Computer Science for All” initiative in Oregon that aims to democratize high school computer science and broaden participation in an academic subject that is one of the most segregated disciplines nationwide, in terms of both race and gender. With no statewide policies to support computing instruction, Oregon’s legacy of computer science education has been marked by both low participation and by rates of underrepresented students falling well-below the already dismal national rates. The study outlined in this paper focuses on how teacher education can support educators in developing knowledge and agency, and impacting policies and practices that broaden participation in computing. In particular, this research seeks to understand two questions. First, how do teachers experience equity-focused professional development in preparation for teaching an introductory course in computer science? Second, this study queries, how do teachers understand their own agency in influencing policies and practices that broaden participation in their specific schools and classrooms? To answer these questions, this inquiry employed a mixed method approach, drawing from surveys, observations, and interview data of two cohorts of teachers who participated in the Exploring Computer Science professional development program. To show the variety of school contexts and situate computer science education in local and place-based policies and practices, three teacher case studies are presented that illustrate how individual teachers, in diverse geographic and demographic settings, are building inclusive computer science opportunities in their schools. The findings reveal that centering equity-focused teacher professional development supports teachers in formulating the confidence, knowledge and skills that lead to inclusive computer science instruction, computer science content, and equity-centered pedagogy. The findings also highlight how school reform in computer science requires not only technical and pedagogical supports and structures, but also a systemic rethinking and reworking of normative and political forces that are part of the fabric of schools. Based on these findings of teacher knowledge and agency, the paper concludes with a presentation of particular statewide policies and practices that are generative in broadening belief systems and expanding political capacity of computer science education to reach all students.